Model Kepemimpinan Kiai Hodri dalam Pengembangan Kualitas Pendidikan Islam Pondok Pesantren - Muhammad faishol; Fathor Rachman; Mohammad Rouf (JSP: Jurnal Studi Pesantren, 2023)
The leadership of kiai plays a central role in developing the quality of pesantren education in the contemporary era. This research analyzes the leadership model of Kiai Hodri in improving the quality of Islamic education at Pondok Pesantren Sabilul Muttaqin Daramista, Lenteng, Sumenep. The research focuses on the leadership type, quality development strategies, and the impact of leadership on pesantren educational transformation. This study employs a qualitative approach with a phenomenological design to understand Kiai Hodri's leadership experience in depth. Data collection was conducted through in-depth interviews with Kiai Hodri, ustadz, santri, and pesantren administrators, participatory observation, and analysis of pesantren policy documentation. Data validity was maintained through source and method triangulation, while data analysis utilized data reduction, data display, and conclusion verification techniques. Findings indicate that Kiai Hodri implements a democratic-charismatic leadership model that combines spiritual authority with a participatory approach. Quality development strategies include transformation of the pesantren community's mindset, enhancement of ustadz competence, development of an integrative curriculum, and improvement of technology-based facilities and infrastructure. Kiai Hodri's transformative leadership has successfully produced graduates with independence in science and technology fields, demonstrating the effectiveness of synthesizing traditional pesantren leadership with contemporary educational innovation.